(untitled) (Marketing Journal, 2025)
This article examines the theoretical foundations of innovation development and the digital economy, as well as their role and interrelation in the modern economic environment. It analyzes the forms of innovation activity and the key components of the digi tal economy, including artificial intelligence, digital payment systems, and 542 information and communication technologies (ICT). Special attention is given to the strategies implemented in Uzbekistan, particularly the "Digital Uzbekistan – 2030" program and the "Innovation Development Strategy." The article concludes that the integration of innovation and digital transformation is a crucial factor in achieving sustainable economic growth.